Beginning Microsoft Word 2010 - Anderson, Ty.; Hart-Davis, Guy.; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; Moodie, Matthew; Parkes, Duncan; et al. (Berkeley, CA : Apress, 2010)
Beginning Microsoft Word 2010 is a visually stimulating introductory guide that teaches the complete Word newbie (as well as slightly experienced yet equally baffled users) what they need to know to write that thesis or proposal tonight. From the absolute basics like installing the software and creating documents to more advanced features like adding images and working with themes, this book is your one-stop source for using Word 2010 effectively. This books shows you what$1 (Bs new in Word 2010$1 (Bincluding advanced features for collaboration on documents and updates to the user interface$1 (Bwhile also providing a solid grounding in overall word processing skills. Using step-by-step instructions as well as visual aids and screenshots, Beginning Microsoft Word 2010 will guide you from a no-nothing newbie to a proficient and knowledgeable Word user.s
The Word 2010 Primer -- Writing and Editing Text Basics -- Adding Style to Documents -- Reusing Content -- Making Your Documents Display Information Effectively -- Completing a Document -- Editing Pictures within Word -- Using Media with Word -- Working with Others -- Taking Your Use of Word to the Next Level.
Keywords: Computer science; Computer Science; Computer Applications